The Effect of Service Quality and Employees’ Performance Towards Community Satisfaction - Ismet Sulila (Journal of International Conference Proceedings (JICP), 2021)
This research aims to find out the effect of service quality employees’ performance towards community satisfaction. It applies quantitative approach. The technique of data analysis is multiple linear regression. There are 25 respondents obtained through purposive sampling technique. The findings reveal that (1) service quality influences towards community satisfaction as much as 28,50%, (2) employees’ performance influences towards community satisfaction as much as 35,70%, (3) service quality and employees’ performance influence towards community satisfaction with R2 value of 64,20%. The results of this research are expected to be the input and reinforcement for the employees at Population and Civil Registration Agency in understanding the importance of improving service and performance quality to meet public satisfaction.